Neural network activity and neurological soft signs in healthy adults - Thomann, Philipp; Hirjak, Dusan; Kubera, Katharina Maria; Stieltjes, Bram; Wolf, Robert Christian (Behavioural brain research, 2015)
Previous neuroimaging studies in schizophrenia have shown that neurological soft signs (NSS) are associated with abnormal brain structure and function, but it remains unclear whether these findings truly reflect pathological processes or if they may be confounded by antipsychotics. To address these issues, structural neuroimaging studies conducted in healthy populations have shown an association between NSS and cortical regions but to date, studies of brain function in healthy participants are scarce. In this study, using functional magnetic resonance imaging we investigated 37 healthy adults under “resting-state” conditions. Functional connectivity of motor cortical and subcortical neural networks was assessed using a group spatial independent component analysis (ICA). NSS were measured using the “Heidelberg Scale”. The relationship between functional connectivity at rest and NSS was analyzed using a regression model where age, gender and movement parameters were included as nuisance variables. We identified 35 stable components, from which five networks of interest were chosen for further analyses. Within three motor cortical networks, negative correlations were found between NSS levels and functional connectivity of the right precuneus, right superior frontal areas, supplementary motor area, and left paracentral gyrus. There were no significant associations between NSS scores and striatal or thalamic connectivity. In conclusion, the data indicate that in healthy young adults NSS are associated with regionally confined levels of cortical activity and not with striatal or thalamic function. The neural mechanisms underlying NSS in healthy individuals appear to rely on cortically mediated motor control and planning to a higher degree than on functions subserved by subcortical structures.
Online 4 November 2014
Gesehen am 30.06.2020